Exploring emotions as social phenomena among Canadian varsity athletes. (November 2016) - Tamminen, Katherine A.; Palmateer, Tess M.; Denton, Michael; Sabiston, Catherine; Crocker, Peter R.E.; Eys, Mark; Smith, Brett
Abstract: Objectives: Athletes are constantly engaging with teammates, coaches, and opponents, and rather than treating emotions as manifested in the individual as is often the case, psychological analyses need to treat emotions as social and relational. The purpose of this research was to explore athletes' accounts of emotions as social phenomena in sport using qualitative inquiry methods. Method: Fourteen Canadian varsity athletes (7 males, 7 females, age range: 18–26 years) from a variety of sports participated in two semi-structured interviews. Data were analyzed using inductive coding, categorization, micro-analysis, and abduction (Mayan, 2009; Strauss & Corbin, 1998). Results: Athletes reported individual and shared stressors that led to individual, group-based, and collective emotions, and they also reported emotional conflict when they simultaneously experienced individual and group-based or collective emotions. Emotional expressions were perceived to impact team functioning and performance, communicated team values, served affiliative functions among teammates, and prompted communal coping to deal with stressors as a team. Factors which appeared to influence athletes' emotions included athlete identity, teammate relationships, leaders and coaches, and social norms for emotion expression. Conclusions: Our study extends previous research by examining emotions as social phenomena among athletes from a variety of sports, and by elaborating on the role of athletes' social identity with regard to their emotional experiences in sport. Highlights: This research explored athletes' accounts of emotions as social phenomena in sport. Experiences of group-based and collective emotions were associated with athletes' social identity as team or group members. Emotions communicated team values, and prompted affiliation and communal coping among teammates. Collective emotional experiences are important for teammate relationships and team performance. Some athletes reported feeling emotional conflict between their individual emotions and the collective emotions of the team.